2016
DOI: 10.1002/adma.201602888
|View full text |Cite
|
Sign up to set email alerts
|

Pure Protein Bilayers and Vesicles from Native Fungal Hydrophobins

Abstract: Pure protein bilayers and vesicles are formed using the native, fungal hydrophobin HFBI. Bilayers with hydrophobic (red) and hydrophilic (blue) core are produced and, depending on the type of core, vesicles in water, oily media, and even in air can be created using microfluidic jetting. Vesicles in water are even able to incorporate functional gramicidin A pores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 47 publications
3
32
0
5
Order By: Relevance
“…The results showed no significant upregulation of autophagy marker genes associated with high hfb gene activity (aerial hyphae) Taken together, the results of the above analyses indicated that HFBs first accumulated in lipid bodies that were internalized in vacuoles and likely gave rise to VMSs. In VMSs, HFBs self-assembled in the hydrophobic/hydrophilic interface led to the lining up of VMS membranes and/or formation of HFB vesicles similar to the bilayer HFB1 vesicles reported by Hähl et al in a cell-free system 32 . In some cells, several VMSs containing HFB vesicles formed gigantic central tonoplasts, as observed in Fig.…”
Section: Hfbs Massively Accumulate In Aerial Hyphae Of Filamentous Fusupporting
confidence: 61%
“…The results showed no significant upregulation of autophagy marker genes associated with high hfb gene activity (aerial hyphae) Taken together, the results of the above analyses indicated that HFBs first accumulated in lipid bodies that were internalized in vacuoles and likely gave rise to VMSs. In VMSs, HFBs self-assembled in the hydrophobic/hydrophilic interface led to the lining up of VMS membranes and/or formation of HFB vesicles similar to the bilayer HFB1 vesicles reported by Hähl et al in a cell-free system 32 . In some cells, several VMSs containing HFB vesicles formed gigantic central tonoplasts, as observed in Fig.…”
Section: Hfbs Massively Accumulate In Aerial Hyphae Of Filamentous Fusupporting
confidence: 61%
“…Ein auf die Doppelmembran gerichteter Flüssigkeitsstrom induziert die Bildung von geschlossenen Vesikeln. – a) verändert nach , b) nach , c) aus …”
Section: Rekordverdächtige Amphiphileunclassified
“…Weiterhin gelang, angeregt durch den Flüssigkeitsstrom aus einer feinen Kanüle, die Bildung stabiler, von Hydrophobin‐Membranen umgrenzter Vesikel mit einem Durchmesser von etwa 100 μm (Abbildung c). In solche Vesikel – mit hydrophiler Oberfläche – konnte das Protein Gramicidin A inseriert werden, das in der Proteinmembran genauso als Ionenkanal funktionierte wie in einer Lipidmembran .…”
Section: Rekordverdächtige Amphiphileunclassified
“…Furthermore, this approach does not require high temperature, pressure, and voltage to fabricate fibers as is necessary for conventional methods . Additionally, the microfluidic platform can be applied to create other bioactive materials, such as particles, liposomes, droplets, and vesicles …”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Additionally, the microfluidic platform can be applied to create other bioactive materials, such as particles, liposomes, droplets, and vesicles. [25,26] Using poly (ε-caprolactone) (PCL) fibrous scaffolds has two main advantages. PCL can be considered as a good candidate for long-term implantable devices due to its slow degradation rate compared to other synthetic polymers, like poly(lactic-coglycolic acid) (PLGA), making the microenvironment less acidic during the degradation process.…”
Section: Introductionmentioning
confidence: 99%